2018
DOI: 10.3892/etm.2018.5839
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent variations of cancellous bone in response to ovariectomy in C57BL/6J mice

Abstract: Abstract. The ovariectomized (OVX) mouse model has been widely accepted to be suitable for the study of postmenopausal osteoporosis. However, whether C57BL/6J mice, a commonly used genetic background mouse strain, is an appropriate model for postmenopausal osteoporosis remains controversial. The present study investigated the effect of the OVX model on alterations in bone density and microarchitecture in C57BL/6J female mice of different ages. C57BL/6J mice were divided into 8-, 12-and 16-week-old groups (OVX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…The age of the mice at the time point of OVX might be regarded as too young and the time span between OVX and the time point of fracture might be regarded as too short. However, the changes in bone turnover rate due to OVX are clearly visible in 8 and 12 weeks old C57Bl/6J mice at the time point of 8 weeks after OVX as described by Zhou and colleagues [53]. Additionally, the skeletal response to OVX was detected already 1 month after OVX surgery [54], demonstrating that our study design is suitable for comparing the influence of sensory and sympathetic neurotransmitters on fracture healing under quasi menopausal conditions.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The age of the mice at the time point of OVX might be regarded as too young and the time span between OVX and the time point of fracture might be regarded as too short. However, the changes in bone turnover rate due to OVX are clearly visible in 8 and 12 weeks old C57Bl/6J mice at the time point of 8 weeks after OVX as described by Zhou and colleagues [53]. Additionally, the skeletal response to OVX was detected already 1 month after OVX surgery [54], demonstrating that our study design is suitable for comparing the influence of sensory and sympathetic neurotransmitters on fracture healing under quasi menopausal conditions.…”
Section: Discussionsupporting
confidence: 66%
“…Experimental protocols and methods were approved and carried out according to the regulations and guidelines of these committees. We used 10 weeks old female mice [53,55,56], kept under standard housing conditions (12h dark/light cycle) with free access to food and water. We used Tac1-/-mice that do not produce SP due to a targeted mutation in the Tachykinin 1 gene [57].…”
Section: Animalsmentioning
confidence: 99%
“…Nevertheless, it is perhaps a bit unexpected that most of the µCT parameters monitored were not altered by OVX given the changes in BMD observed; however, the C57BL/6 mouse has been shown previously to exhibit marginal (i.e., not significant) changes in many parameters measured by µCT after OVX, depending on the age, the bone site measured and the observation period post-OVX. Thus, Zhou et al (2018) demonstrated that in 24-week-old C57BL/6 analyzed 8 weeks post-OVX, the only femoral µCT parameters that are significantly different are volumetric BMD and Tb.Sp, but not BV/TV, Tb.N or Tb. Th (although younger 16-and 20-week-old mice do exhibit differences in some of these other bone parameters).…”
Section: Figure 10mentioning
confidence: 89%
“…The prevalence of OA in postmenopausal women is higher than that in men. Ovariectomy significantly reduced the production of estrogen in mice, resulting in increased bone resorption mediated by subchondral bone osteoclasts, resulting in increased subchondral bone loss and bone microstructure deterioration, thereby promoting articular cartilage degeneration and inducing osteoarthritis ( 31 , 38 ). Osteoporosis (OP) is characterized by increased bone loss, deterioration of bone microarchitecture and an increased risk of fragility fractures ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty mice were randomly divided into 3 groups: A sham-operated group (n=20), OVX+vehicle group (n=20), and OVX+DHA group (n=20). According to the literature, the mice were operated from the abdominal cavity through the back to remove the bilateral ovaries ( 12 , 31 ). The same procedure was performed in the sham-operated group, except that the bilateral ovaries were only removed.…”
Section: Methodsmentioning
confidence: 99%